Biographical memoirs. (National Academies Press, 2005)
"Published since 1877, Biographical Memoirs are brief biographies of deceased National Academy of Sciences members, written by those who knew them or their work. These biographies provide a personal and scholarly view of the lives and work of America's most distinguished scientists and a biographical history of science in the United States."